Analisis Teknik Penerjemahan Mandarin – Indonesia di dalam E-Comerce pada Produk Mi - Sitohang, Junita Laurentina; Julina, Julina; Adryani Nasution, Vivi (Al Makki Publisher, 2025)
This study aims to analyze the translation techniques used in naming nood le products from Mandarin to Indonesian on the Shopee e-commerce platform. This study uses a qualitative method with a phenomenological approach to explore the meaning behind the translation process as a phenomenon that occurs in the practice of online buying and selling. The main data in this study is in the form of the names of Chinese noodle products that have been translated and displayed in the Shopee application. Data collection techniques were carried out through observation and documentation, while data analysis used the Miles, Huberman, and Saldana (2014) model which included data reduction, data presentation, and conclusion drawn. The results of the study show that there are various translation techniques such as discursive creation, borrowing, linguistic compression, amplification, reduction and adaptation used to adapt the product name to the target cultural and linguistic context. The application of these techniques not only aims to convey meaning, but also to attract consumer interest and increase the marketability of products in the Indonesian market.